Investigation of the mechanism of aerodynamic separation of rice husks from brown rice following paddy hulling by coupled CFD-DEM. (June 2022) - Chen, Peiyu; Han, Yanlong; Jia, Fuguo; Zhao, Dan; Meng, Xiangyi; Li, Anqi; Chu, Yanhao; Zhao, Hongwei
Abstract : Aerodynamic separation of rice husks from brown rice grains after paddy husking is one of the important processes in rice processing. So far, the realisation of complete separation of rice husks from brown rice is still a challenging task. In this study, computational fluid dynamics (CFD) and discrete element method (DEM) were used to simulate the process, and the simulation results were verified by experiment. Based on this, the process of the separation of rice husks from the mixture was clarified. The mechanisms of brown rice loss and the rice husk retention were explored by analysing the collision process of the husks and rice in the separation duct. The interaction between mixture particles and airflow was explored. The results show that feeding of the mixture particles led to the decrease in the airflow velocity; however, it did not disturb the airflow stability or produce obvious turbulence. Adjustment of airflow velocity significantly influences the separation; nonetheless, incomplete separation of rice husks and brown rice still remains. The mechanism of brown rice loss and rice husk retention in the separation process occurred simultaneously to some extent in the separation region. As a result, brown rice and rice husk entered the opposite regions and collided with each other in their opposite region, respectively. Highlights: The separation process of mixture particles was studied by DEM-CFD simulation method. Feeding mixture doesn't disturb the airflow stability and produce turbulence. Adjusting the airflow can not solve the problem of incomplete separation. Brown rice losing is caused by rice husk collision. The rice husk remaining is caused by brown rice coercion and collision.